Physiological arterial pressure improves renal performance during normothermic machine perfusion in a porcine kidney DCD model - Yitian Fang; Gisela Ambagtsheer; Lin Xia; Marian C. Clahsen-van Groningen; Robert C. Minnee; Ron W.F. de Bruin (Heliyon)
Background: Normothermic machine perfusion (NMP) provides a platform for kidney quality assessment. Donation after circulatory death (DCD) donor kidneys are associated with great ischemic injury and high intrarenal resistance (IRR). This experimental study aims to investigate the impact of different perfusion pressures on marginal kidney function and injury during NMP. Methods: Twenty-seven slaughterhouse porcine kidneys were retrieved and subjected to 60 min of warm ischemia time to mimic DCD condition. These kidneys were randomized into 75 mmHg (subphysiological, n = 9), 95 mmHg (physiological, n = 9), and 115 mmHg NMP (high physiological, n = 9). Renal function and injury were assessed during NMP. Results: Three groups showed comparable IRR, with the 115 mmHg group exhibiting the highest blood flow. The 95 mmHg group [0.48 (0.36–1.15) ml/min/100g] and 115 mmHg group [0.93 (0.45–1.41) ml/min/100g] showed significantly higher creatinine clearance compared to the 75 mmHg group [0.16 (0.08–0.37) ml/min/100g] during the first hour of NMP (p = 0.049, p = 0.009, respectively). The 115 mmHg group exhibited significantly higher oxygen consumption compared to the 75 mmHg group at 30 min of NMP [1.37 (1.05–1.92) versus 0.72 (0.61–0.82) mlO2/min/100g, p = 0.009]. Perfusate neutrophil gelatinase-associated lipocalin (NGAL) levels were consistently lowest in the 95 mmHg group and highest in the 75 mmHg group. Aspartate aminotransferase (AST) levels of the 115 mmHg group were significantly higher than the 75 mmHg group. Conclusions: For kidneys with high IRR, both 95 mmHg and 115 mmHg perfusion pressures enable an early improvement in renal hemodynamics and function compared to 75 mmHg during NMP, while a high physiological perfusion can cause additional injury.